Affection perceived and felt: Representations of primary education students - Osti, Andréia [UNESP]; Tassoni, Elvira Cristina Martins (FapUNIFESP (SciELO), 2019)
Affections experienced by students in the school environment influence learning. This study sought to investigate how students perceive the learning environment and what feelings are involved in the relationship with learning, as well as to measure gender differences. Participants were 312 students from the 5th grade of primary education of three municipal schools in the interior of São Paulo state. The Free Word Association Technique was applied and results show that boys have more negative feelings and perceptions regarding school and the relationship with the teacher. Girls have more positive feelings and negative ones are directed towards themselves. By discussing the relationships between affectivity and cognition, this research contributes to the field of teacher education.
Afectividad percibida y sentida: Representaciones de alumnos de enseñanza fundamental
Affectivité perçue et ressentie: Représentations des élèves de l’enseignement fondamental
Keywords: Affection; Interpersonal relationships; Learning experience; Representation